A kinetic model for growth and biosynthesis of medium-chain-length poly-(3-hydroxyalkanoates) in Pseudomonas putida - Annuar, Mohamad Suffian Mohamad; Tan, Irene Kit Ping; Ibrahim, Shaliza; Ramachandran, K.B. (Brazilian Society of Chemical Engineering, 2008)
A kinetic model is presented giving a mathematical description of batch culture of Pseudomonas putida PGA1 grown using saponified palm kernel oil as carbon source and ammonium as the limiting nutrient. The growth of the micro-organism is well-described using Tessier-type model which takes into account the inhibitory effect of ammonium at high concentrations. The ammonium consumption rate by the cells is related in proportion to the rate of growth. The intracellular production of medium-chain-length poly-(3-hydroxyalkanoates) (PHAMCL) by P. putida PGA1 cells is reasonably modeled by the modified Luedeking-Piret kinetics, which incorporate a function of product synthesis inhibition (or reduction) by ammonium above a threshold level.